TCP Splicing for Application Layer Proxy Performance - Maltz, Dave; Bhagwat, Pravin (J. High Speed Networks, 1998)
Application layer proxies already play an important role in today's networks, serving as rewalls and HTTP caches | and their role is being expanded to include encryption, compression, and mobility support services. Current application layer proxies su er ma jor performance penalties as they spend most of their time moving data back and forth between connections; context switching and crossing protection boundaries for each chunk of data they handle. We present a technique called TCP Splice that provides kernel support for data relaying operations which runs at near router speeds. In our lab testing, we nd SOCKS rewalls using TCP Splice can sustain a data throughput twice that of normal rewalls, with an average packet forwarding latency 30 times less